From Stability To Volatility: The Asymmetric Effects Of Macroeconomic Factors On Indonesia's Sustainable Stocks - Sakuntala, Dwita; Theodora, Eka Martyna; Hou , Amin; Tampubolon, Arsyaf (Jurnal Ekonomi, 2024)
SRI and Sharia stocks in Indonesia are part of the green assets that have outperformed other stocks. However, they are also volatile and vulnerable to shocks. This study examines the asymmetric effects of macroeconomic uncertainty-specifically domestic interest rates, global uncertainty, and domestic exchange rates-together with environmental degradation factors on the SRI and Sharia stock markets in Indonesia. The findings show that exchange rate asymmetry significantly impacts the SRI and Shariah stock markets, as evidenced by the sizable coefficients. In the SRI stock market, positive exchange rate shocks are found to have a negative impact in both the short and long run. In contrast, in the Islamic stock market, the effect of positive exchange rate shocks is only seen in the short run. This evidence suggests that an increase in positive exchange rate shocks will lead to a decline in both the SRI and Islamic stock markets. When the domestic exchange rate appreciates, Indonesian exports become more expensive in the international market, thus reducing the competitiveness of firms in export-dependent markets, which then affects their stock prices. Moreover, in the long run, negative shocks related to global uncertainty negatively impact the Islamic stock market. This finding indicates that when the global economic environment deteriorates and overseas investments are perceived as risky, domestic investors-especially those who are risk averse-tend to shift their investments to domestic Islamic assets, which they perceive as more reliable.